ANALYSIS OF THE GALODO FLOOD DISASTER FROM YEAR 1979 AND YEAR 2009 PASIE LAWEH, BATUSANGKAR - Kevin Eduardo (SEMESTA: Journal of Science Education and Teaching, 2020)
The purpose of this paper is to analyze the flash floods from 1979 and 2009 to explore local wisdom in the community related to the science of natural events (Galodo). This observation activity was carried out by the Galodo incident in Pasie Laweh, Sungi Tarab, Tanah Datar. Negeri Pasie Laweh (Pasla) is a beautiful village located at the foot and slopes of Mount Merapi, one of the highest mountains in West Sumatra Province. Cool air, beautiful and seductive scenery, and residents who always adhere to the philosophy of "Adat basandi syarak, Syarak basandi kittabullah". This means that in addition to having to consider the factor of traditional istadat that has been passed down and carried out in this area, the population also adheres to the holy book of the Qur'an as the basis of life. So that the thick Minangkabau nuances are clearly visible in this village.